Assessment and prediction of concrete flow and pumping pressure in pipeline. (March 2020) - Secrieru, Egor; Mohamed, Wesam; Fataei, Shirin; Mechtcherine, Viktor
Abstract: In work at hand, a site suitable, scientifically-based methodology to characterise and predict fresh concrete pumping behaviour was developed and verified. The properties of the lubricating layer (LL) formed during pumping and consequently reducing the friction at the pipe wall-to-concrete interface were investigated and quantified. The flow pattern of fresh concrete was modelled experimentally and numerically. Instrumented full-scale pumping experiments were performed simultaneously with rheological tests on fresh concrete before and after pumping. The comparison of predicted and actual pressure-flow rate curves showed for these methods a highly accurate predictive capacity. Hence, the authors strongly advocate the application of the scientifically based, ready-to-use methodology developed here in construction practice as a part of the future in situ rheology monitoring concept.